Is the stemless humeral head replacement clinically and radiographically a secure equivalent to standard stem humeral head replacement in the long-term follow-up?: a prospective randomized trial - Uschok, Stephan; Magosch, Petra (Journal of shoulder and elbow surgery, 2017)
Background - Stemless humeral head replacement represents a young generation of shoulder arthroplasty. This study evaluated the differences of this new stemless design compared with the fourth-generation standard stemmed design. - Methods - Total shoulder arthroplasty was performed in 20 patients with a stemless shoulder prosthesis (group 1) and in 20 patients with a standard stem humeral head replacement (group 2). Twenty-nine patients were examined clinically and radiographically at a minimum follow-up of 2 years and a minimum follow-up of 5 years. Functional results were assessed using the age- and gender-related Constant Score (CS). The radiographic analysis used native x-rays in 3 planes. - Results - The postoperative CS improved significantly in both groups, with no significant difference between the minimum of 2-year and 5-year follow-up. The difference in the CS, its subcategories, and active range of motion between the implant groups was not significant. A significant difference was observed in the radiographic analysis for the zone adjacent to the humeral calcar, with a lower bone mineral density in 41% of group 2 and in 0% in group 1. Radiolucent lines were statistically more frequent in group 2. No statistical differences were observed between the implant groups for the change of the inclination angle, the medial offset, and the lateral offset. - Conclusion - Both implants showed consistently good functional and radiologic results without a significant difference and achieved an anatomic reconstruction of the humeral head geometry in the coronal plane.